Exponential stabilization of fractional-order continuous-time dynamic systems via event-triggered impulsive control - Yu, Nanxiang; Zhu, Wei (Nonlinear Analysis: Modelling and Control, 2022)
Exponential stabilization of fractional-order continuous-time dynamic systems via eventtriggered impulsive control (EIC) approach is investigated in this paper. Nonlinear and linear fractional-order continuous-time dynamic systems are studied, respectively. The impulsive instants are determined by some given event-triggering function and event-triggering condition, which are dependent on the state of the systems. Sufficient conditions on exponential stabilization for nonlinear and linear cases are presented, respectively. Moreover, the Zeno-behavior of impulsive instants is excluded. Finally, the validity of theoretical results are also illustrated by some numerical simulation examples including the synchronization control of fractional-order jerk chaotic system.
Keywords: event-triggered; impulsive control; fractional order; exponential stabilization; synchronization